The Analysis of Kangaroo Mother Care Implementation at Public Health Center in Indonesia - Paradillah, Indri; Martha, Evi; Ramadhan, Farandi Agesti; Tenriana, Irene; Syahbana, Lutfi Rinaldi; Lubis, Izmi Arisa Putri; Pratomo, Hadi (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Infant mortality is one of the sensitive indicators to know the degree of health of a country and even to measure the level of progress of a nation. The Low Birth Weight Babies (LBW) are the highest cause of infant mortality in Depok until it reaches 81 cases in 2019. One of the efforts made by public health office to reduce the infant mortality rate is to use Kangaroo Mother Care. This research aims to analyze the implementation of Kangaroo Mother Care Program in public health center in Depok, Indonesia. Methods: The method of study is qualitative with purposive sampling approach.Result: The results showed that the informants were not aware of the existence of Mayor Regulation Number 89 year 2020 regarding Kangaroo Method Care. Health workers do not yet have sufficient knowledge about the implementation of the Kangaroo Method of Care. The implementation of the Kangaroo Method of Care is still not supported by complete facilities. Human Resources is also still inadequate.Conclusion: The conclusion of this research is the Kangaroo Method Care program has not run optimally. There needs to be an effort to improve the implementation of the Kangaroo Method Care program at the public health center.